INTERAKSI PARTAI POLITIK DAN PENGUSAHA DALAM REKRUTMEN PENCALONAN KEPALA DAERAH DI INDONESIA - Bahtiar, M. Teguh Setyadi; Muhammad (FISIP Universitas Malikussaleh, 2025)
This study aims to explore and describe the forms of interaction between businessmen as strongmen and political parties in the political recruitment activities of regional head candidates in Indonesia, and seeks to describe how the exchange of interests affects the political recruitment of regional head candidates in Indonesia, as well as its impact on the quality of local democracy. This research is qualitative research using literature study. The results of this study found that the form of interaction between political parties and entrepreneurs in the recruitment of candidates for regional heads in Indonesia. First, the interaction between political parties and entrepreneurs as financial sponsors. Entrepreneurs fund political parties through a mutually beneficial reciprocal mechanism. Second, the interaction between political parties and entrepreneurs as candidates or candidate supporters. Entrepreneurs as candidates for regional heads or sponsors of regional head candidates, tend to find it easier to get recommendations from political parties in the recruitment of regional head candidacies, through this reciprocal mechanism. Meanwhile, the implications for the quality of local democracy of this interaction. First, the development of political dynasties from among entrepreneurs. Second, it prevents the existence of diverse political actors. Third, the potential for political corruption.